2014
DOI: 10.1097/sap.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Satisfaction After Total Skin-Sparing Mastectomy and Immediate Expander-Implant Reconstruction

Abstract: After TSSM and immediate reconstruction, patient satisfaction with their breasts, as well as psychosocial and sexual well-being, returns to baseline by 1 year. Although overall nipple satisfaction is high, patients often report dissatisfaction with nipple position and sensation; appropriate preoperative counseling is important to set realistic expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 22 publications
5
40
0
2
Order By: Relevance
“…27 A recent survey study by our group assessing satisfaction of patients undergoing TSSM and immediate expander-implant reconstruction in prior years, using the BREAST-Q questionnaire, highlighted the importance of attaining correct nipple position in this population. 28 In this study, mean nipple satisfaction score was 74.1 at 1 year, with 85% of patients reporting satisfaction with the overall appearance of their nipples. However, at this 1-year mark, 63% of patients expressed dissatisfaction with nipple position on the reconstructed breast.…”
Section: Discussionmentioning
confidence: 94%
“…27 A recent survey study by our group assessing satisfaction of patients undergoing TSSM and immediate expander-implant reconstruction in prior years, using the BREAST-Q questionnaire, highlighted the importance of attaining correct nipple position in this population. 28 In this study, mean nipple satisfaction score was 74.1 at 1 year, with 85% of patients reporting satisfaction with the overall appearance of their nipples. However, at this 1-year mark, 63% of patients expressed dissatisfaction with nipple position on the reconstructed breast.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, although in this study we did not assess differences in patient-reported outcomes or satisfaction with these 2 techniques to see if satisfaction correlates with observer-reported aesthetic scoring, we are currently expanding our use of patient-reported outcomes tools in our practice to further address patient satisfaction after TSSM. 4 In cases of delayed, 2-stage autologous reconstruction after TSSM, the tissue expander is placed in the subpectoral plane at time of mastectomy, given the high rate of postmastectomy radiation in these patients, and the desire to minimize expander extrusion (which did not occur in any of the patients in our study), particularly in the setting of the thin mastectomy skin flaps created with TSSM approaches. In such cases, at the time of second-stage expander removal and exchange with autologous flap, it is our routine to perform a pectoralis major muscle transfer.…”
Section: Discussionmentioning
confidence: 96%
“…1 The benefits of TSSM, like standard nipple-sparing mastectomy (NSM), include obviating the need for nipple reconstruction and achieving excellent aesthetic outcomes and high rates of patient satisfaction. [2][3][4][5] Oncologic concerns regarding incomplete resection or increased recurrence rates after TSSM and NSM have been assuaged in multiple single-institution studies and systematic reviews tracking outcomes after TSSM and immediate breast reconstruction. [6][7][8][9] Breast reconstruction after TSSM presents a unique set of challenges.…”
mentioning
confidence: 99%
“…Evaluated against a baseline population, patients scored higher on average in physical functioning, vitality, emotional well-being, and general health categories (Dao & Verheyden, 2005). Interestingly, in their experience Peled et al found that patients with greater preoperative breast size and/or more significant ptosis reported decreased nipple satisfaction as measured by the BREAST-Q (Peled et al, 2014).…”
Section: Discussionmentioning
confidence: 99%